Reproducibility of fundus autofluorescence measurements obtained using a confocal scanning laser ophthalmoscope. Issue 3 (1st March 1999) - Lois, Noemi; Halfyard, Anthony S; Bunce, Catey; Bird, Alan C; Fitzke, Fredrick W
Abstract : AIM: To evaluate the reproducibility of the background fundus autofluorescence measurements obtained using a confocal scanning laser ophthalmoscope. METHODS: 10 normal volunteers and 10 patients with retinal disease were included in the study. One eye per subject was chosen randomly. Five images of the same eye of each individual were obtained, after pupillary dilatation, by two investigators using a confocal scanning laser ophthalmoscope. Background fundus autofluorescence was measured at 7 degrees temporal to the fovea in normal volunteers and between 7 and 15 degrees temporal to the fovea in patients. Within session reproducibility of the measurements obtained by each investigator and interobserver reproducibility were evaluated. RESULTS: For investigator 1 the median values of fundus autofluorescence obtained were 31.9 units for normal volunteers and 27.3 units for patients. The median largest difference in readings in normal volunteers was 5.7 units (range 1.4–13.5 units) and in patients 4.2 units (1.5–15.1 units). For investigator 2 the median values of fundus autofluorescence obtained were 28.9 units for normal volunteers and 27.4 units for patients. The median largest difference in readings in normal volunteers was 3.6 units (2.7–11.7 units), and in patients 4.1 units (1.5–9.3 units). The median interobserver difference in readings in normal volunteers was 3.3 units and for patients 6.6 units. The median greatest interobserver difference in measurements obtained for normal volunteers was 8.8 units (8.4–23.0 units) and for patients 11.1 units (7.1–40.8 units). CONCLUSION: Within session reproducibility of the measurements of background fundus autofluorescence was satisfactory. Although interobserver reproducibility was moderate, the variability of the measurements of fundus autofluorescence between observers appears to be small when compared with variation in fundus autofluorescence with age and disease.